2006
DOI: 10.1111/j.1365-2133.2005.07101.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Cw*06 is not essential for streptococcal-induced psoriasis

Abstract: Thus, not all patients with streptococcal-related psoriasis carry Cw*06. The role of Cw*06 in psoriasis, if any, has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
3
16
1
4
Order By: Relevance
“…Note in this context that we selected M protein and keratin peptides that were predicted to bind relatively strongly with HLACw*0602, which is carried by ,50% of patients with chronic psoriasis (27), although this may vary between populations (28,29). Second, we selected for this study patients who reported aggravation of their disease in association with sore throat, which only applies to ∼40% of patients with chronic psoriasis in Iceland (R.H. Thorleifsdottir, J.H.…”
Section: Discussionmentioning
confidence: 99%
“…Note in this context that we selected M protein and keratin peptides that were predicted to bind relatively strongly with HLACw*0602, which is carried by ,50% of patients with chronic psoriasis (27), although this may vary between populations (28,29). Second, we selected for this study patients who reported aggravation of their disease in association with sore throat, which only applies to ∼40% of patients with chronic psoriasis in Iceland (R.H. Thorleifsdottir, J.H.…”
Section: Discussionmentioning
confidence: 99%
“…Aber auch akut-exanthematische Schübe einer chronischen Plaquepsoriasis werden vornehmlich durch Streptokokkeninfektionen getriggert [54], und Patienten mit chronischer Plaquepsoriasis zeigen eine höhere Inzidenz streptogener Pharyngitiden oder Kolonisierung [17]. Dabei ist v. a. die HLA-Cw6-assoziierte Typ-1-Psoriasis mit frühem Erkrankungsbeginn und positiver Psoriasisfamilienanamnese mit Streptokokkeninfektionen assoziiert, während diese für Typ-2-Psoriasis (spä-ter Erkrankungsbeginn, negative Familienanamnese, kein HLA-Cw6) keine oder kaum eine Rolle spielen [15,60].…”
Section: Tab 1 Häufigkeit Von Streptokokkeninfektionen Bei Psoriasisunclassified
“…A number of clinical reports suggest that bacterial infection can trigger psoriasis, and it has been known for a long time that acute exacerbation of psoriasis may follow streptococcal infection [18,19,20,21]. The resulting psoriasis is commonly of the guttate pattern, but existing plaque psoriasis may also be exacerbated [3, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting psoriasis is commonly of the guttate pattern, but existing plaque psoriasis may also be exacerbated [3, 21]. …”
Section: Discussionmentioning
confidence: 99%